Postprandial Hyperchylomicronemia and Thin-Cap Fibroatheroma in Nonculprit Lesions: A Multivessel Optical Coherence Tomography Study. Issue 8 (August 2018) - Kurihara, Osamu; Okajima, Fumitaka; Takano, Masamichi; Kato, Katsuhito; Munakata, Ryo; Murakami, Daisuke; Miyauchi, Yasushi; Emoto, Naoya; Sugihara, Hitoshi; Seino, Yoshihiko; Shimizu, Wataru
Abstract : Objective—: Although postprandial hypertriglyceridemia can be a risk factor for coronary artery disease, the extent of its significance remains unknown. This study aimed to investigate the correlation between the postprandial lipid profiles rigorously estimated with the meal tolerance test and the presence of lipid-rich plaque, such as thin-cap fibroatheroma (TCFA), in the nonculprit lesion. Approach and Results—: A total of 30 patients with stable coronary artery disease who underwent a multivessel examination using optical coherence tomography during catheter intervention for the culprit lesion were enrolled. Patients were divided into 2 groups: patients with TCFA (fibrous cap thickness ⩽65 µm) in the nonculprit lesion and those without TCFA. Serum remnant-like particle-cholesterol and ApoB-48 (apolipoprotein B-48) levels were measured during the meal tolerance test. The value of remnant-like particle-cholesterol was significantly greater in the TCFA group than in the non-TCFA group ( P =0.045). Although the baseline ApoB-48 level was similar, the increase in the ApoB-48 level was significantly higher in the TCFA group than in the non-TCFA group ( P =0.028). In addition, the baseline apolipoprotein C-III levels was significantly greater in the TCFA group ( P =0.003). These indexes were independent predictors of the presence of TCFA (ΔApoB-48: odds ratio, 1.608; 95% confidence interval, 1.040–2.486; P =0.032; apolipoprotein C-III: odds ratio, 2.581; 95% confidence interval, 1.177–5.661; P =0.018). Conclusions—: Postprandial hyperchylomicronemia correlates with the presence of TCFA in the nonculprit lesion and may be a residual risk factor for coronary artery disease.